City Hospital emergency room - Swersey, Arthur J. ([London] : SAGE, 2016)
Covering many relevant issues, this study examines the delivery of emergency room services.
Originally Published in: Swersey, A. J. (2009). City Hospital Emergency Room. 09-041. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Quality control -- Case studies; Business consultants -- Case studies; Hospitals -- Administration -- Case studies